De retirantes a aldeias urbanas: parentesco, poder e educação entre os Mundurukú das Praias do Índio e do Mangue em Itaituba - PA - SOUSA, Walter Lopes de (Universidade Federal do Pará, 2014)
This work is a study about two Mundurukú communities, Praia do Índio e Praia do Mangue. They are located in urban area in Itaituba – PA, Brazil. The contact between tribal and national societies, planted a lot of problems, prejudicing the social group’s own reproduction. However these groups making an effort to recreate their Mundurukú identity through Mundurukú language teaching in their Indians schools. This study was coming true during the Socials Science Master Program course of Universidade Federal do Pará, in Anthropology subject, from March 2006 to March 2008. The research was divided in two stages. The fist one consisted in researches in libraries, bookshops and internet about specific Anthropology texts. The second stage was fieldwork in Itaituba’s Indian communities. Two months were taking during the University breaking periods. However I stayed more four months before the Master Course start too. Twelve families representing 258 people were interviewed. The results of this research showed the Mundurukú traditional institutions can adapt themselves to the urban situation. A new social order was born due to the interaction and contact with national society. This new social order keeps traditional Mundurukú and national society features. In this urban context, despite of everything, we can see that the Mundurukú traditional institutions mainly keep marking their powers spaces that are still governed by kinship, by clans and by Mundurukú local leaderships ('cacicado').